Interface Engineering between the Metal-Organic Framework Nanocrystal and Graphene toward Ultrahigh Potassium-Ion Storage Performance - Xiao, Peitao; Li, Shuo; Yu, Chengbing; Wang, Ying; Xu, Yuxi (ACS nano, 2020)
The potassium-ion battery (PIB) has been recognized as a promising low-cost and high-energy battery; however, it suffers from a relatively low capacity and inferior cycling performance compared with current electrode materials. Herein, we report an effective interface engineering strategy to prepare metal-organic framework (MOF) nanocrystals tightly encapsulated by reduced graphene oxide (rGO) via strong chemical interaction as a free-standing anode for PIB. Based on experimental analysis and theoretical calculations, we systematically investigated the effect of the chemical-bonded interface between MOF nanocrystals and conductive rGO and revealed that the strong chemical interface can substantially enhance the adsorption energy and ion transport kinetics of the potassium ion within the MOF nanocrystals compared to the physical mixture of MOF and rGO with almost the same microscopic morphologies. As a result, such an MOF-rGO hybrid with strong interfacial chemical couplings delivered an ultrahigh reversible capacity of 422 mAh g-1 at 0.1 A g-1, superior rate performance (202 mAh g-1 at 5 A g-1), and outstanding long-term cycling performance (an ultralow decay rate of 0.013% per cycle after 2000 cycles at 2 A g-1), which are not only significantly better than those of the physical mixture of MOF/rGO but also among the best for anodes for PIB reported thus far.
Keywords: chemical bonding coupling; interface engineering; graphene; metal−organic framework; high-performance potassium-ion anode